(untitled) (Scientific journal of the Fergana State University, 2025)
The article describes the distribution of geochemical elements on the dried bottom of the Aral Sea. For the first time in the Aral Sea, the amount of elements in the soil, the process of their movement, geochemical barriers, their role in regulating the composition and properties of the soil, and geochemical flows were studied. These elements enter the sea with the waters of the Amu Darya and Syr Darya and atmospheric precipitation, as a result of which Sr, Ba, Rb, La, Hf, Cs, Sm, Tb, and U accumulate in the soil.